What makes Candida auris pan-drug resistant? Integrative insights from genomic, transcriptomic, and phenomic analysis of clinical strains resistant to all four major classes of antifungal drugs - Rhodes,J; Jacobs,J; Dennis,EK; Manjari,SR; Banavali,NK; Marlow,R; Rokebul,MA; Chaturvedi,S; Chaturvedi,V (Antimicrobial Agents and Chemotherapy, 2024)
The global epidemic of drug-resistant Candida auris continues unabated. The initial report on pan-drug resistant (PDR) C. auris strains in a hospitalized patient in New York was unprecedented. PDR C. auris showed both known and unique mutations in the prominent gene targets of azoles, amphotericin B, echinocandins, and flucytosine. However, the factors that allow C. auris to acquire pan-drug resistance are not known. Therefore, we conducted a genomic, transcriptomic, and phenomic analysis to better understand PDR C. auris. Among 1,570 genetic variants in drug-resistant C. auris, 299 were unique to PDR strains. The whole-genome sequencing results suggested perturbations in genes associated with nucleotide biosynthesis, mRNA processing, and nuclear export of mRNA. Whole transcriptome sequencing of PDR C. auris revealed two genes to be significantly differentially expressed—a DNA repair protein and DNA replication-dependent chromatin assembly factor 1. Of 59 novel transcripts, 12 transcripts had no known homology. We observed no fitness defects among multi-drug resistant (MDR) and PDR C. auris strains grown in nutrient-deficient or -enriched media at different temperatures. Phenotypic profiling revealed wider adaptability to nitrogenous nutrients and increased utilization of substrates critical in upper glycolysis and tricarboxylic acid cycle. Structural modeling of a 33-amino acid deletion in the gene for uracil phosphoribosyl transferase suggested an alternate route in C. auris to generate uracil monophosphate that does not accommodate 5-fluorouracil as a substrate. Overall, we find evidence of metabolic adaptations in MDR and PDR C. auris in response to antifungal drug lethality without deleterious fitness costs.